Ordenamento do uso e ocupação do solo na planície fluviolagunar do rio Betume e adjacências - Lima, Luana Pereira (2017)
Coastal environments are complex due to their natural dynamics, fragilities and multiple socioeconomic interests. They are peculiar environments and of differentiated character, that must be considered in their singularity, and they need special attention for a correct planning and management. The new rationality of occupation of the coastal environments associates the demand of a leisure society with a demand for zones of work and housing. Given this, there is a need for studies that present proposals for environmental planning aiming at a balance between the use and maintenance of natural resources. The purpose of this study was to analyze in an integrated way the environmental and socioeconomic dynamics of the fluvio lagoon plain associated with the Betume River and its surroundings from the perspective of land use and land use planning. In order to do so, the systemic approach was adopted as a way of researching the landscape, which made it possible to understand the reality and thus propose a zoning resulting from the application of the pressure-state-impact-response methodology. Bibliographical review, documentary research, field work, cartographic document elaboration, were the methodological procedures adopted and subsidized the integrated analysis of the environmental and social dimensions that culminated in a zoning proposal. The plain formed by fluvio lagoons deposits associated with the Betume River has a geological-geomorphologic evolution developed from events of transgressions and marine regressions of the Quaternary and is inserted between dunes strands in marine and paleo cliffs terraces of the Barreiras Group. Its structure points to a level of marked environmental fragility. In contrast, the uses attributed to this environment have shown growth, namely: activities and interests aimed at tourism; Primary economic activities of fishing, shrimp farming, pasture, agriculture and plant extractive activities. The level of occupation is unevenly distributed, as is the intensity of modification and degradation. Zoning, from environmental and socioeconomic diagnostics, proposes guidelines for land use and occupation in order to sustain environmental quality.